El efecto del uso de la estrategia de mapas mentales en el logro y la retención del efecto del aprendizaje para alumnos de quinto grado en matemáticas y su tendencia hacia ello (Journal of the College of Basic Education, 2022)
Conducted a search in one of the Directorate of Education Maysan primary schools, and was designed to investigate The impact of the use strategy of mind mapping in achievement and effect of learning, for students in the fifth grade in mathematics and their inclination towards it. where the sample search (39) students, so they distributed to the two groups, first experimental (20) studied student mind maps according to the strategy, and the second control (19) pupils studied according to traditional teaching methods (the classical). Reward where the researcher two sets of search variables (chronological age, previous achievement in mathematics, and the degree of intelligence, parents academic level), as the work of a researcher to control the associated variables that may affect the course of the experiment, and thus on their results. In order to achieve the research objectives were prepared two instruments research (achievement test for math, tilt the scale towards it) where the number of paragraphs of the test (35) paragraph checksums objective of multiple choice, either the number of items tilt the scale towards mathematics reached (20) item by Likert scale Quintet , it was verified validity and reliability of utilities for them. After the end of the probationary period, which lasted five weeks, it was applied two instruments research on the basic sample, and the most important results that have been reached, it is no difference statistically significant between the mean scores of the research sample in achievement test students and measure inclination towards mathematics experimental and control groups, and in favor of the group pilot, as well as the survival effect of learning for the experimental group after applied to the experimental group after a two-week period. It means that the use of mind maps in teaching pupils have a positive impact on the collection of mathematics and retain information learned and improved leanings toward art, to the fifth grade primary. In light of the findings it was written by the researcher's conclusions, as a number of recommendations and proposals.